The Tragedy of Modern Man in Death of a Salesman - Djaidja Rim, Djaidja Aissa (My University, 2020)
The modern American drama has brought new concepts and emerged modern thoughts to the American theatre. Arthur Miller's Death of a Salesman has marked one of the most influential and interesting plays in American history and literature. This thesis examines if Willy Loman, the Protagonist in Death of a Salesman, is a modern tragic hero. It investigates how and why Willy Loman is a tragic hero and how he was emerged to be a tragic hero although he is a common man. The paper also depicts the causes which led to Willy Loman' suicide at the end of the play. Willy Loman is a common man, struggles for his success, suffers and lives the pain of his failure, and ends his life in the end of the play to benefit his family, presents him as a "modern tragic hero" in modern tragedy by Arthur Miller's concept. Basically, Willy's denial, disappointment of not being capable to cope and his illusion about how the world has become and his past memories have led to his death. Willy has tragic life. He could never accept his failure and could not accept the way things have become. Eventually, this led to his downfall. This play portrays a modern tragedy with a common person who struggles to fit in a modern world with modern mentality.
Keywords: Key words: modern man, modern tragedy.